2016
DOI: 10.1007/s10549-016-3911-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase II studies of two different schedules of dasatinib in bone metastasis predominant metastatic breast cancer: SWOG S0622

Abstract: Purpose Bone metastases from breast cancer are common, causing significant morbidity. Preclinical data of dasatinib, an oral small molecule inhibitor of multiple oncogenic tyrosine kinases, suggested efficacy in tumor control and palliation of bone metastases in metastatic breast cancer (MBC). This clinical trial aimed to determine whether treatment with either of 2 dose schedules of dasatinib results in a progression free survival (PFS) > 50% at 24 weeks in bone metastasis-predominant MBC, to evaluate the tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Patients in the advanced stage in various solid tumors show resistance to treatment, and a number of studies have investigated novel antitumor agents, with a particular focus on molecularly targeted drugs. In recent years, Src inhibitors have been studied extensively ( 8 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients in the advanced stage in various solid tumors show resistance to treatment, and a number of studies have investigated novel antitumor agents, with a particular focus on molecularly targeted drugs. In recent years, Src inhibitors have been studied extensively ( 8 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have revealed no effect of dasatinib alone on breast, pancreatic, colorectal and ovarian tumor progression, overall survival or progression-free survival ( 8 , 12 , 13 , 15 ). This may be due to the activation of other signaling molecules, such as the Src family kinases Janus kinase and FGR ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in the release of matrix-derived growth factors, such as transforming growth factor-β1 (TGF-β1), which further stimulate tumor growth [6,7]. Although novel therapeutic options and targets are emerging (e.g., tyrosine kinase inhibitors, microRNAs [8][9][10][11]), the disease remains incurable once osteolytic lesions have developed.…”
Section: Introductionmentioning
confidence: 99%